PENGARUH GADGET TERHADAP BERKEMBANGNYA POLA BERPIKIR ANAK DIDIK DI SMPN 3 SIMPANG HILIR KABUPATEN KAYONG UTARA - Dewi Andriani; Junaidi H Matsum; Aminuyati Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the effect of gadgets on the development of the mindset of students at SMPN 3 Simpang Hilir, North Kayong Regency. This quantitative research is a correlation research. The population of all students in Class VIII A of SMPN 3 Simpang Hilir, Kayong Utara Regency, 28 sample students taken in this study were all students. Researched Gadget (X) Development of Mindset (Y). Data collection using a questionnaire instrument. Instrument validation uses expert judgment and reliability with internal consistency using Cronbach's Alpha technique. The researchers concluded that: 1) The use of gadgets by students at SMPN 3 Simpang Hilir, North Kayong Regency, resulted in the highest category of 21 (75%) students having a medium category. 2) The development of the mindset of students at SMPN 3 Simpang Hilir, North Kayong Regency, the results obtained with the highest category of 17 (61%) students category. 3) Based on Simple Linear Regression Analysis, the effect of using gadgets on the development of students' mindsets is obtained by the equation 28.831 + 0.400X which means the constant value is 28.831 The value of the regression coefficient of the variable use of gadgets is positive, namely 4.106. The large influence of gadgets on the development of students' mindsets based on the results of the determination test was 39.3% while the remaining 60.7% was influenced by other factors not examined in this study.Keywords: Effect of Gadget, Social Studies, Development of Mindset.